2006
DOI: 10.5688/aj700233
|View full text |Cite
|
Sign up to set email alerts
|

Learning Motivational Interviewing: Scripting a Virtual Patient

Abstract: Objectives. This article describes a written assignment for a first-year professional communication course to facilitate the understanding and mastery of motivational interviewing in dealing with patient ambivalence and resistance. The goal was to immerse students in how motivational interviewing differs from traditional biomedical counseling with regard to phrasing individual responses to the patient and managing the flow of interaction. Methods. Students were required to write a script for a working prototyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 7 publications
2
48
0
Order By: Relevance
“…14 Increased confidence and knowledge following the use of an online case program and the MirixaPro platform was also found by Begley and colleagues. 12 They found that students had a greater appreciation of MTM as a whole and felt they could use MTM in their future practice, which is congruent with the participant response in this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…14 Increased confidence and knowledge following the use of an online case program and the MirixaPro platform was also found by Begley and colleagues. 12 They found that students had a greater appreciation of MTM as a whole and felt they could use MTM in their future practice, which is congruent with the participant response in this study.…”
Section: Discussionsupporting
confidence: 77%
“…[7][8] Online virtual-patient learning experiences increase the knowledge of health professionals, including pharmacists seeking professional development. [10][11][12][13][14] The Theory of Planned Behavior states that a person's actions may be predicted based on their beliefs about a subject. Assessment of these beliefs will predict whether an educational intervention will alter the participant's future behavior in terms of intent to apply the new knowledge gained.…”
Section: Introductionmentioning
confidence: 99%
“…While these projects have found great success, their approach would not succeed for VH conversation training applications; novices (e.g. students) are not generally motivated to engage directly in the process of conversational modeling [8]. We find the solution to motivating users in Lois von Ahn's ESP Game [7].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Projects in military [1], psychology [3], and medicine [2,8] have been created with significant collaborative effort from both domain experts and computer science experts. These publications report that it is logistically difficult and time consuming to create the necessary conversational corpora [1][2][3]8].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…33 Scriptwriting was used in 2 studies as a written method of reinforcing verbal communication skills in a communication course. 21,39 The subcategory of clinical writing skills incorporated all formats specifically directed toward pharmacy practice. These included SOAP (subjective, objective, assessment, plan) notes, 16,52 patient care plans 20,71 and written patient medical histories.…”
Section: Description and Categorization Of Communication Skillsmentioning
confidence: 99%